RURALITY AS THE CORE OF TOURISM PRODUCT – USEFULNESS OF GEOGRAPHIC AND ECONOMIC APPROACHES - Majewski, Janusz (Acta Scientiarum Polonorum. Oeconomia, 2010)
Rural tourism can be defined in geographical and economic terms. In both approaches the definition of “rurality” is fundamental for understanding specificity of rural tourism. Geographers represent supply-side and economists demand-side approach. The latter can be used for building rural tourism product because of market research as the base. The main conclusion from market research is that landscape has become the main reason of choosing rural tourism by clients. Landscape can give tourists many experiences like tranquillity which is rather state of mind than objective value. Thus, experiencing tranquillity is the core of rural tourism product. The article reviews criteria of tranquillity and mapping based on British achievements.